Ordovician gas exploration breakthrough in the Gucheng lower uplift of the Tarim Basin and its enlightenment - Wang Zhaoming; Yang Haijun; Qi Yingmin; Chen Yongquan; Xu Yanlong (Natural Gas Industry B, 2014)
A steady high yield natural gas flow was tapped in the Ordovician strata of Well Gucheng 6 drilled in the Gucheng lower uplift in the Tarim Basin in 2012, marking the discovery of another carbonate gas exploration field after the other two fields in the middle and northern Tarim Basin (the so called Tazhong and Tabei in the industry). The exploration in the Gucheng lower uplift has experienced three stages: the first stage, marine facies clastic exploration from 1995 to 2003, focusing on the Devonian Donghe sandstone lithologic traps, the Silurian overlapping lithologic traps, and the Upper Ordovician shelf slope turbidites; the second stage focusing on the reef shoal carbonate reservoirs from 2003 to 2006, during which oil and gas were first discovered in Well Gucheng 4; the third stage can be divided into two periods, in the first period, deeper insight into interbed karstification reservoir exploration, intense research on tricky seismic issues, selection of favorable zones, and 3D seismic deployment in advance laid a robust foundation for breakthroughs in oil and gas exploration; and during 2009–2012, through an in-depth investigation, Well Gucheng 6 was drilled, bringing about the major breakthrough in oil and gas exploration in this study area. This success proves that the Lower Paleozoic carbonate rocks in the Gucheng area have good geological conditions and broad prospect for oil and gas exploration, which give us enlightenment in three aspects: a. new insight into geologic understanding is the prerequisite of exploration breakthrough; b. addressing bottleneck technologies, and acquiring 3D seismic data are the guarantees of exploration breakthrough; and c. emancipation of mind and persistent exploration are key to the findings in new domains.